The development of teacher leadership in Kansas during unprecedented times of change - Mitchell, Tamra Lynn (Kansas State University, 2021)
The 2020–2021 COVID-19 pandemic created a crisis that tested teacher leaders, building leaders, and school culture in ways that will take years to analyze. In this qualitative focus group study, teachers working in Kansas throughout the pandemic shared their perspectives on leadership development. The teachers reported taking on roles and responsibilities beyond what they could have imagined, affecting their professional relationships with students, families, colleagues, and the greater community. Teachers said they enjoyed successes and learned painful lessons from their failures. When discussing changes in their leadership, they reported growth in their skills and confidence regarding communication, collaboration, and social-emotional development. When discussing the role of their principals, most described principals who generally supported students and teachers. However, many had difficulty explaining how their principals intentionally contributed to their leadership growth during this time. Those who could add to this topic said that shared leadership, relational trust, and intentional opportunities to practice leadership skills with support, coaching, and feedback were needed to help them feel successful.
Developing teacher leadership during unprecedented times of change
Keywords: Teacher leadership; Leadership; School culture; Principal leadership; School improvement; Pandemic education; Crisis educational leadership